The effects of coronary occlusion location on the RR signal. - Claria, F. (IEEE Engineering in medicine and biology magazine)
We carry out the study of the energy contribution of the RR signal in the three frequency bands (LF, MF, and HF) during percutaneous transluminal coronary angioplasty. Furthermore, variables based on instantaneous frequency and on group delay computed from RR signal in the three frequency bands are analyzed. All these variables are calculated by applying the Choi-Williams distribution to the RR signal. The purpose of studying these variables is to provide a punctual location of the energy in the time-frequency plane, since this can allow different kinds and locations of coronary lesions to be distinguished.